2010
DOI: 10.1007/s11095-010-0219-2
|View full text |Cite
|
Sign up to set email alerts
|

Decrease of Plasminogen Activator Inhibitor-1 May Contribute to the Anti-Invasive Action of Cannabidiol on Human Lung Cancer Cells

Abstract: Our data provide evidence for a hitherto unknown mechanism underlying the anti-invasive action of cannabidiol on human lung cancer cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
76
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(83 citation statements)
references
References 42 publications
1
76
1
1
Order By: Relevance
“…Recent studies found that Jesengsingi-Hwan prevents oxaliplatin-induced peripheral neuropathy through the functional alteration in TRPA1 and TRPM8 [116] and can reduce paclitaxel-induced peripheral neuropathy by suppressing TRPV4 expression [117]. Moreover, the TRPV1-mediated anti-cancer effects of cannabidiol have been reported in multiple cancer cell lines, including breast [118], lung [119,120], and colon [121]. Inflammatory and neuro-immune responses also play important roles in the development and progression of CIPN [122].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies found that Jesengsingi-Hwan prevents oxaliplatin-induced peripheral neuropathy through the functional alteration in TRPA1 and TRPM8 [116] and can reduce paclitaxel-induced peripheral neuropathy by suppressing TRPV4 expression [117]. Moreover, the TRPV1-mediated anti-cancer effects of cannabidiol have been reported in multiple cancer cell lines, including breast [118], lung [119,120], and colon [121]. Inflammatory and neuro-immune responses also play important roles in the development and progression of CIPN [122].…”
Section: Discussionmentioning
confidence: 99%
“…Locally produced fibrinolytic enzyme could degrade the extracellular matrix barrier and thereby facilitate local invasion and distant metastasis. [6][7][8][9] Many articles have reported that plasma D-dimer levels can be used to judge the disease stage, prognosis of many solid tumors and predict the incidence of thrombotic events in cancer patients. [3][4][5][10][11][12][13][14] Research on the application value of plasma D-dimer in colorectal cancer was carried out in the 1990s.…”
Section: Discussionmentioning
confidence: 99%
“…In certain cancer cell lines, the ability of CBD to inhibit cancer cell viability/proliferation has been reversed in the presence of antagonists for CB 2 , TRPV1, TRPM8, COX-2, and PPRÎł (Table 1). Lung cancer cell lines appear to be particularly responsive to reversal of the anti-invasive effects of CBD in culture with antagonists to CB 1 , CB 2 , and TRPV1 (Ramer et al, 2010a; Ramer et al, 2010b). Currently, only two studies have investigated receptor dependence of CBD-dependent antitumor activity in vivo .…”
Section: Non-psychoactive Plant-derived Cannabinoids As Inhibitorsmentioning
confidence: 99%